Laparoscopic excision of congenital choledochal cyst in children and modified hepaticojejunostomy with an unequal length of the jejunal loop (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Complete excision biliary-enteric reconstruction is necessary for a congenital choledochal cyst (CC) to prevent recurrent cholangitis, acute pancreatitis, and cholangiocarcinoma. Among various reconstructions, this study aims to evaluate the therapeutic effect of unequal length jejunal loop for the biliary reconstruction of congenital choledochal cyst.Method: The clinical data of 56 cases of congenital choledochal cyst treated in the pediatric surgery department of Children's Hospital Affiliated to Zheng Zhou University were retrospectively analyzed. All cases were treated with choledochal cyst resection and unequal length jejunal loop biliary reconstruction, including 51 cases with laparoscopic surgery and 5 cases with traditional surgery.Result: Choledochal cyst resection and unequal length jejunal loop biliary reconstruction were successfully completed in all cases. One case of laparoscopic operation developed biliary fistula on the 3rd day after the operation, and the biliary fistula healed after conservative treatment for 8 days. The other cases recovered smoothly without obvious complications. No contrast agent bile loop reflux was found in upper gastrointestinal angiography.Conclusion: The modified jejunal loop biliary reconstruction has many advantages over the traditional biliary reconstruction, which is worthy of clinical application.